2008
DOI: 10.1530/rep-08-0018
|View full text |Cite
|
Sign up to set email alerts
|

Caput epididymitis but not orchitis was induced by vasectomy in a murine model of experimental autoimmune orchitis

Abstract: Immunization of mice with viable syngeneic testicular germ cells (TGC) alone can induce autoimmune responses against autoantigens of both round and elongating spermatids, resulting in the development of experimental autoimmune orchitis (EAO). Histological lesions in this EAO model without an adjuvant are characterized by lymphocytic infiltration into the testes, spermatogenic disturbance, and a complete lack of epididymitis. In this study, we investigated the effects of vasectomy (Vx) on TGC-induced EAO expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…In this EAO model, lymphocytic inflammation starts from the tubuli recti and then spreads to the peripheral testes; however, the epididymides and vasa deferentia are not involved (Itoh et al, 1995). It was recently found that vasectomy after immunization with testicular germ cells changed the histopathological mode of inflammation, significant lymphocytic infiltration being induced in the initial segment of the epididymis instead of by EAO (Qu et al, 2008). These phenomena suggest that the microenvironment of testis and the initial segment of epididymis are sensitive to inflammatory cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…In this EAO model, lymphocytic inflammation starts from the tubuli recti and then spreads to the peripheral testes; however, the epididymides and vasa deferentia are not involved (Itoh et al, 1995). It was recently found that vasectomy after immunization with testicular germ cells changed the histopathological mode of inflammation, significant lymphocytic infiltration being induced in the initial segment of the epididymis instead of by EAO (Qu et al, 2008). These phenomena suggest that the microenvironment of testis and the initial segment of epididymis are sensitive to inflammatory cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…874,922 Likewise, mice with a targeted deletion of the immunoregulatory AIRE transcription factor developed sperm antibodies and leukocytic infiltrates in the epididymis, without orchitis. 923 Vasectomized A/J mice that have been immunized with syngeneic testicular spermatogenic cells develop epididymitis independent of orchitis, 924,925 suggesting that the epididymis can be the primary site of immune reactions following vasectomy, as well. The epididymis is also more susceptible than the testis to spermatic granuloma formation in humans and in experimental mice.…”
Section: Autoimmunity In the Epididymis Vas Deferens And Prostatementioning
confidence: 99%
“…Real-time RT-PCR (TaqMan) analysis for relative determination of the mRNA level was performed using the standard curve method [17]. The detection of cytokine mRNAs was performed using proprietary predeveloped TaqMan primers (IFN-γ (ID: Mm00801778-m1), TNF-α (ID: Mm00443258-m1), IL-1α (ID: Mm00443258-m1), IL-1β (ID: Mm00434228-m1), IL-6 (ID: Mm00446190-m1), TGF-β (ID: Mm0041724-m1) and β-actin (ID: Mm00607939-s1); PE Applied Biosystems, Foster City, CA, USA).…”
Section: Real-time Rt-pcrmentioning
confidence: 99%